Pengaruh Pemberian Hidroterapi Rendam Kaki Air Hangat terhadap Tekanan Darah pada Penderita Hipertensi - Rahmat Hidayat Djalil; Faradila M. Suranata; Nabilla Aqikah Putri Binol (Jurnal Kesehatan Amanah, 2025)
Hypertension is one of the non-communicable diseases that serves as a leading cause of death in many countries. One simple method that can help reduce blood pressure is hydrotherapy through warm foot immersion. This study aimed to determine the effect of this therapy on blood pressure among hypertensive patients at Bahu Public Health Center. The research employed a quasi-experimental design with a one-group pre-post test approach involving 15 respondents. Data were analyzed using the McNemar test with a significance level of 0.05. The findings revealed a significant decrease in blood pressure after the intervention, with p-values of 0.02 for systolic pressure and 0.04 for diastolic pressure. These results demonstrate that warm foot immersion is effective in helping reduce blood pressure in individuals with hypertension. Thus, this simple and easily applied therapy has the potential to serve as a complementary method in hypertension management at primary healthcare facilities. It is hoped that the community and healthcare providers will consider this non-pharmacological therapy as an alternative for helping control blood pressure.